2022
DOI: 10.3390/vaccines10091566
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy among Health Professional Students: Cross-Sectional Data from the First Wave of the HOLISTIC Cohort Study

Abstract: Vaccine hesitancy has been observed around the world, but there is a paucity of data among a broad range of U.S. health professional students. The goal of this report is to present findings about COVID-19 vaccine hesitancy among a cross-section of U.S. health professional students and determine if hesitancy varies by demographic characteristics, health science college, and other factors. A cross-sectional analysis of HOLISTIC Cohort Study participants enrolled from April 14 2021 to May 5 2021 at seven health s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The HOLISTIC Cohort Study enrolled students across seven health science colleges (applied health sciences, dentistry, medicine, nursing, pharmacy, public health, and social work) at the University of Illinois Chicago, a U.S. Department of Education designated minority-serving institution. 34 Students were eligible to enroll in the HOLISTIC Cohort Study if they were age 18 years or older and enrolled full-or part-time in a health science program that prepares its graduates to enter a healthcare profession.…”
Section: Study Populationmentioning
confidence: 99%
“…The HOLISTIC Cohort Study enrolled students across seven health science colleges (applied health sciences, dentistry, medicine, nursing, pharmacy, public health, and social work) at the University of Illinois Chicago, a U.S. Department of Education designated minority-serving institution. 34 Students were eligible to enroll in the HOLISTIC Cohort Study if they were age 18 years or older and enrolled full-or part-time in a health science program that prepares its graduates to enter a healthcare profession.…”
Section: Study Populationmentioning
confidence: 99%
“…The issue of race and ethnicity is arising worldwide; Drobniewski et al (2022) identified a greater reluctance to be vaccinated among healthcare students from ethnic communities. Moreover, in a study by Loizzo et al (2022), an increased concern about the risk of taking the new COVID-19 vaccine was presented by Asian and Hispanic American health students. Similarly, a significantly smaller proportion of healthcare professionals of ethnic minorities were vaccinated than white workers (Martin et al, 2021).…”
Section: Ethnicity and Religiositymentioning
confidence: 99%